2019
DOI: 10.1126/science.aau8650
|View full text |Cite
|
Sign up to set email alerts
|

The NASA Twins Study: A multidimensional analysis of a year-long human spaceflight

Abstract: To understand the health impact of long-duration spaceflight, one identical twin astronaut was monitored before, during, and after a 1-year mission onboard the International Space Station; his twin served as a genetically matched ground control. Longitudinal assessments identified spaceflight-specific changes, including decreased body mass, telomere elongation, genome instability, carotid artery distension and increased intima-media thickness, altered ocular structure, transcriptional and metabolic changes, DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
617
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 711 publications
(658 citation statements)
references
References 151 publications
36
617
3
2
Order By: Relevance
“…Alteration of the gene expression pattern and cell morphology within the periosteum after loading suggests that these skeletal stem cells sense loading stimuli and remodeling 63 65 . In addition, mitochondrial function is likely to be affected by microgravity 24 , 37 , 66 , and the role of mitochondrial energy production mediated by oxidative phosphorylation in skeletal muscle stem cells (SMSCs) has been investigated. SMSCs are normally cell-cycle arrested but differentiate to generate myocytes upon muscle damage, and along with self-renewing SMSCs form new myofibers.…”
Section: Recent Jaxa Space Missions Related To Muscle and Bonementioning
confidence: 99%
“…Alteration of the gene expression pattern and cell morphology within the periosteum after loading suggests that these skeletal stem cells sense loading stimuli and remodeling 63 65 . In addition, mitochondrial function is likely to be affected by microgravity 24 , 37 , 66 , and the role of mitochondrial energy production mediated by oxidative phosphorylation in skeletal muscle stem cells (SMSCs) has been investigated. SMSCs are normally cell-cycle arrested but differentiate to generate myocytes upon muscle damage, and along with self-renewing SMSCs form new myofibers.…”
Section: Recent Jaxa Space Missions Related To Muscle and Bonementioning
confidence: 99%
“…The response of biological matter to ionizing radiation is of fundamental interest to many fields, ranging from radiation oncology, 1 x-ray diffraction imaging, 2 and human space flight. 3 The dynamics in a molecule that are triggered by the formation of deep valence holes, i.e., by ionization beyond the highest occupied molecular orbital (HOMO), are of particular relevance for highly energetic ionizing radiation. Deep valence holes can be caused either by the direct interaction with extreme ultraviolet light or by secondary ionizations, e.g., by photoelectrons or Auger electrons following core-level ionization.…”
Section: Introductionmentioning
confidence: 99%
“…Since those initial evaluations, scientific progress has led to the advancement of physical examination in spaceflight. An interesting example was the NASA "Twins Study" [19]. This study was based on the very genuine idea, to investigate the effects of spaceflight in two identical twins, where the first is bound to Earth and the second remains in space for one year.…”
Section: Using Gravitational Force (G) An Experimental Variablementioning
confidence: 99%
“…This study was based on the very genuine idea, to investigate the effects of spaceflight in two identical twins, where the first is bound to Earth and the second remains in space for one year. Yet, the idea moved further on by using all available biomedical technologies, which included simple hematological and biochemical analysis, transcriptomic analysis, epigenomic, immunophenotype, metabolomics, microbiomics, proteomics, physiology and telomeric analysis [19]. The study showed that Earth-bound physiology and spaceflight physiology differ, and it has been apparent that microgravity affects the magnitude of the human physiology and not only isolated physiological systems.…”
Section: Using Gravitational Force (G) An Experimental Variablementioning
confidence: 99%
See 1 more Smart Citation